2012
DOI: 10.1097/tp.0b013e318263ad7a
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 in Solid-Organ Transplantation

Abstract: Human T-cell lymphotrophic virus (HTLV)-1 has been reported after solid-organ transplantation, with a related fatal outcome in less than five cases. The natural history of HTLV-1 transmission from donor to recipient is unknown in this setting, because available screening platforms are suboptimal in low-prevalence areas and there is a lack of long-term follow-up. Minimizing organ wastage due to false-positive screening and avoiding donor-derived HTLV-associated diseases remain the goal. To date, only six HTLV-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Although there are reports of disease transmission to six organ recipients from four donors, only one of whom had confirmed HTLV infection, no case of recipient death by infection with HTLV has yet been reported (D) . ( 73 , 74 , 106 , 107 ) Thus, some countries with a low prevalence of HTLV infection (United States and England) and an insufficient number of donors to meet the increasing demand for transplant organs allow the performance of transplants without previous knowledge of the HTLV status of the donor (D) . ( 73 , 74 , 106 , 107 )…”
Section: Part 3: Criteria For Potential Donor Selectionmentioning
confidence: 99%
“…Although there are reports of disease transmission to six organ recipients from four donors, only one of whom had confirmed HTLV infection, no case of recipient death by infection with HTLV has yet been reported (D) . ( 73 , 74 , 106 , 107 ) Thus, some countries with a low prevalence of HTLV infection (United States and England) and an insufficient number of donors to meet the increasing demand for transplant organs allow the performance of transplants without previous knowledge of the HTLV status of the donor (D) . ( 73 , 74 , 106 , 107 )…”
Section: Part 3: Criteria For Potential Donor Selectionmentioning
confidence: 99%
“…As a result, the true incidence of severe S. stercoralis infection might have been underestimated. Second, we were unable to collect data on the human T-lymphotropic virus (HTLV) infection status of the recipients, a variable that has been shown to affect the clinical course of S. stercoralis infection [39,40]. Such information is not systematically collected for transplant recipients in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Such information is not systematically collected for transplant recipients in Brazil. Although the actual prevalence of HTLV infection after kidney transplantation is unknown, many studies have found low rates of HTLV seropositivity in transplant recipients [39,40]. Although there have been some reports of myelopathy after donor-transmitted infection, it seems that the clinical course of infection in recipients testing positive for HTLV prior to transplantation is benign even under immunosuppression [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations